ANALISIS PENGARUH PENGUNGKAPAN CSR, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anggit Widyamurti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study aims to analyse the effect of CSR disclosure, managerial ownership, and institutionalownership on the value of mining company listed in Jakarta Stock Exchange. The population of thisstudy are all 40 companies listed Jakarta Stock Exchange (JSE) in 2012-2014. The sample of thisstudy are 10 companies selected by using purposive random sampling technique. Method of dataanalysis used is multiple linear regression with SPSS 21 Program. The result shows thatmanagerial ownership variable has significant effect on the value of company. While CSR disclosureand isntitutional ownership do not significantly affect the value of company. The value of R squareis 50,6 % which means that the rest 49,4 % is influenced by other variables.Keywords: CSR Disclosure, Mangerial Ownership, Institutional Onwership, The value of company.